Numerical study of sediment suspension affected by rigid cylinders under unidirectional and combined wave–current flows - Lou, Sha; Chen, Xiaolan; Zhou, Shengyu; Ma, Gangfeng; Liu, Shuguang; Radnaeva, Larisa Dorzhievna; Nikitina, Elena; Fedorova, Irina Viktorovna (Frontiers in Marine Science, 2023)
An improved formulation for incipient sediment suspension considering the effect of cylinder density (i.e., solid volume fraction) is employed to simulate the bottom sediment flux in the flow with cylinders. The proposed model is calibrated using laboratory measurements under unidirectional and combined wave-current flows in previous studies (Chen et al., 2020; Lou et al., 2022), and validated using experimental datasets under unidirectional flows in Lu (2008). It is proved that the effects of cylinders on sediment suspension can be accounted for through a modified critical Shields number, and the proposed model is capable of simulating sediment suspension under both unidirectional and combined wave–current flows reasonably well with the model skills and the coefficients of determination greater than 0.8.